Pseudopotential Calculations of the Band Structure and Fermi Surface of Mercury - Jones, John Conrad (My University, 1970)
The energy bands and Fermi surface of mercury have been calculated using local and non-local pseudopotentials. The non-local pseudopotentials were an approximation in which the repulsive potentials of the outer atomic core states were explicitly represented by non-local projection operators.
A search was made for the regions of parameter space where the pseudopotential generated a Fermi surface having a good fit to the experimental magneto-acoustic calipers and de Haas-van Alphen extremal cross sectional areas.
De Haas-van Alphen frequencies and cyclotron masses were calculated for symmetry planes using a local pseudopotential.
General questions of pseudopotential theory, the symmetry of the energy bands, the occurrence of degeneracies, and the influence of spin-orbit coupling are also considered.
Keywords: physics; pseudopotential calculation; band structure; Fermi surface; mercury